MDR/XDR-TB management of patients and contacts: Challenges facing the new decade. The 2020 clinical update by the Global Tuberculosis Network. (March 2020) - Migliori, Giovanni Battista; Tiberi, Simon; Zumla, Alimuddin; Petersen, Eskild; Chakaya, Jeremiah Muhwa; Wejse, Christian; Muñoz Torrico, Marcela; Duarte, Raquel; Alffenaar, Jan Willem; Schaaf, H. Simon; Marais, Ben J.; Cirillo, Daniela Maria; et al.
Highlights: Updated clinical guidance on MDR-TB is needed. Several new MDR-TB diagnostics have been recently approved by WHO to complement existing tools. To design a regimen, 4–5 active drugs are needed with a treatment duration up to 24 months. Post-treatment sequelae might require pulmonary rehabilitation. LTBI management and infection control are core elements of the MDR-TB public health approach. Abstract: The continuous flow of new research articles on MDR-TB diagnosis, treatment, prevention and rehabilitation requires frequent update of existing guidelines. This review is aimed at providing clinicians and public health staff with an updated and easy-to-consult document arising from consensus of Global Tuberculosis Network (GTN) experts. The core published documents and guidelines have been reviewed, including the recently published MDR-TB WHO rapid advice and ATS/CDC/ERS/IDSA guidelines. After a rapid review of epidemiology and risk factors, the clinical priorities on MDR-TB diagnosis (including whole genome sequencing and drug-susceptibility testing interpretations) and treatment (treatment design and management, TB in children) are discussed. Furthermore, the review comprehensively describes the latest information on contact tracing and LTBI management in MDR-TB contacts, while providing guidance on post-treatment functional evaluation and rehabilitation of TB sequelae, infection control and other public health priorities.